1974
DOI: 10.1139/o74-012
|View full text |Cite|
|
Sign up to set email alerts
|

Fifty Years of Biochemistry. A Personal Account

Abstract: This year ( 1973) marks the 50th anniversary of my first publications, one of which (with M. Dixon: "A new type of reduction oxidation system; cysteine and glutathione") caused quite a stir and gut me in touch with L. Michaelis, of Michaelis-Menten fame.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A reduction in neurotransmission efficacy might arise from a rerouting of the neurotransmitters for metabolic purposes as has been proposed to account for impaired neurotransmission in the brain during hypoglycaemia (Quastel, 1974). In support of this idea, the overall metabolic status of brain slices remained stable during hypoglycaemia while synaptic transmission was disrupted (Lewis et al.…”
Section: Glutamate Catabolism and Retinal Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in neurotransmission efficacy might arise from a rerouting of the neurotransmitters for metabolic purposes as has been proposed to account for impaired neurotransmission in the brain during hypoglycaemia (Quastel, 1974). In support of this idea, the overall metabolic status of brain slices remained stable during hypoglycaemia while synaptic transmission was disrupted (Lewis et al.…”
Section: Glutamate Catabolism and Retinal Functionmentioning
confidence: 99%
“…As glutamate is the major retinal excitatory neurotransmitter, one possibility is that the b‐wave loss reflects altered neurotransmission between photoreceptors and ON‐bipolar cells (Slaughter & Miller, 1981; Stockton & Slaughter, 1989; Robson & Frishman, 1995). Reduced neurotransmission might occur secondary to increased glutamate oxidation to provide metabolic substrates (Quastel, 1974); thus cellular localization would allow the identification of specific metabolic pathways within neuronal or glial cells. We have previously demonstrated that, secondary to 4‐CIN application, inhibiting glutamate‐utilizing enzymes suppressed the b‐wave recovery induced by exogenous substrates (Bui et al.…”
Section: Introductionmentioning
confidence: 99%